2020
DOI: 10.1007/s10751-020-01711-5
|View full text |Cite
|
Sign up to set email alerts
|

Recent experiments at the JYFLTRAP Penning trap

Abstract: The JYFLTRAP double Penning trap mass spectrometer at the Ion Guide Isotope Separator On-Line (IGISOL) facility offers excellent possibilities for high-precision mass measurements of radioactive ions. Around 400 atomic masses, including around 50 isomeric states, have been measured since JYFLTRAP became operational. JYFLTRAP has also been used as a high-resolution mass separator for decay spectroscopy experiments as well as an ion counter for fission yield studies. In this contribution, an overview of recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 68 publications
(113 reference statements)
0
9
0
Order By: Relevance
“…This study was inspired by the theoretical findings reported in [23]. The measurement confirmed that the decay is energetically allowed with an ultra-low value of 0.44 (31) keV, which makes this first-forbidden unique transition with a simple universal spectral shape a potential candidate for antineutrino-mass measurements with almost an order of magnitude lower value than in presently running or planned direct (anti)neutrino-mass experiments [28]. Also, the electron capture of 159 Dy (3∕2 − ) to the 5∕2 − state in 159 Tb was recently studied at JYFLTRAP [29].…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…This study was inspired by the theoretical findings reported in [23]. The measurement confirmed that the decay is energetically allowed with an ultra-low value of 0.44 (31) keV, which makes this first-forbidden unique transition with a simple universal spectral shape a potential candidate for antineutrino-mass measurements with almost an order of magnitude lower value than in presently running or planned direct (anti)neutrino-mass experiments [28]. Also, the electron capture of 159 Dy (3∕2 − ) to the 5∕2 − state in 159 Tb was recently studied at JYFLTRAP [29].…”
Section: Introductionmentioning
confidence: 58%
“…The EC value of 111 In, the mass difference of the parent nucleus 111 In and its EC decaying daughter 111 Cd, was measured at the new Ion Guide Isotope Separator On-Line facility (IGISOL) utilizing the JYFLTRAP double Penning trap mass spectrometer [30,31], at the University of Jyväskylä [32,33]. A primary beam of protons with an energy of 40 MeV from the K-130 cyclotron impinged into a naturally abundant indium target with a thickness of a few mg/cm 2 at the entrance of the IGISOL gas cell [34].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The first ultra-low Q-value decay, 115 In (9/2 + , ground state) → 115 Sn (9/2 + , excited state), was discovered by Cattadori et al [26] and the ultra-low Q value was confirmed by the JYFLTRAP Penning trap [27] and the FSU Penning trap [28]. The second ultra-low Q-value case of 135 Cs (7/2 + , ground state) decaying to 135 Ba (11/2 − , second excited state) was dis-covered at JYFLTRAP [21,29] recently. These are the only two cases that are confirmed to possess ultra-low Q values from direct measurements, and they both belong to the category of β − decay.…”
Section: Introductionmentioning
confidence: 87%
“…Since atomic masses obtained via nuclear reaction data are not always reliable, and because the mass of 114 Cd was determined from an older mass spectrometry technique, a direct Penning trap measurement of the 115 Cd Q value is called for. Recently, the ground-state Q value of 135 Cs was measured with the JYFLTRAP Penning trap and the Q value of the potential UL decay branch was determined to be Q UL = 0.44 (31) keV [23], showing that it is indeed energetically allowed with Q UL < 1 keV.…”
Section: Introductionmentioning
confidence: 99%
“…The JYFLTRAP group recently ruled out potential UL Q value decays in 72 As [29], and showed that 159 Dy does have an electron capture decay branch to an excited state in the daughter with a Q UL value of around 1 keV [30]. They are also investigating other candidates [31].…”
Section: Introductionmentioning
confidence: 99%